1991
DOI: 10.4319/lo.1991.36.3.0413
|View full text |Cite
|
Sign up to set email alerts
|

The major and minor element geochemistry of Lake Baikal

Abstract: A comprehensive, joint Soviet-American study of the chemistry of Lake Baikal, the world's deepest (1,632 m) lake, was carried out in July 1988. In this paper, we report the major, minor, and preliminary trace element concentrations for three profiles obtained at or near the deepest and central part of the three major basins of the lake. With the exception of Ba, the distributions of major and minor elements were homogeneous, displaying no variations greater than analytical uncertainties. Average concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(67 citation statements)
references
References 20 publications
5
59
1
Order By: Relevance
“…The hydrologic balance and the outlet configuration of the lake make it difficult to change lake level climatically. Evaporation is less than one-sixth of the outflow (Kozhov 1963), and the mean residence time of water in the lake is only 300-400 years Faulkner et al 1991). No evidence exists for anything other than a dilute, through-flowing lake controlled by the level of its outlet, which could easily accommodate higher outflow without significant changes in lake level, during the last several hundred thousand years.…”
Section: Lake Level Tectonics and Turbiditesmentioning
confidence: 99%
“…The hydrologic balance and the outlet configuration of the lake make it difficult to change lake level climatically. Evaporation is less than one-sixth of the outflow (Kozhov 1963), and the mean residence time of water in the lake is only 300-400 years Faulkner et al 1991). No evidence exists for anything other than a dilute, through-flowing lake controlled by the level of its outlet, which could easily accommodate higher outflow without significant changes in lake level, during the last several hundred thousand years.…”
Section: Lake Level Tectonics and Turbiditesmentioning
confidence: 99%
“…Of the minor elements (Ba, Rb, Li, Sr, U) profiled in 1988, only Ba, decreasing gradually with depth, displayed nonconservative behavior (Falkner et al 1991). At the central and southern basin stations, levels decreased more sharply in near botto.m waters for which transmissometry indicated elevated particle concentrations (W. Gardner pers.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fixation rates inferred from oxygen consumption rates and nutrient considerations confirmed previous reports that the lake is oligotrophic and suggested that nitrate is ithe limiting nutrient . Based on values reported in the literature for riverine inputs, the major ions in Baikal seemed to be dominated by riverine throughput and to reside in the lake on the order of the water residence time of 330 yr (Falkner et al 1991). At least for the present, hydrothermal activity, which has been observed to occur in Frolikha Bay at the northern end of Baikal (Crane et al 1991 a;Golubev 1978Golubev , 1984, appeared to play a minor role in major ion cycling in the lake as a whole compared to riverine throughput (Falkner et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 mg/l , suggesting large-scale vertical convection in the lake. The mean residence time of major ions in the lake is estimated to be 330 years (Falkner et al, 1991). Nevertheless deep water exchanges rapidly.…”
Section: Introductionmentioning
confidence: 99%